Longitudinal Survey of Fecal Microbiota in Healthy Dogs Administered a Commercial Probiotic - Ciaravolo, Susan; Martínez-López, Lina María; Allcock, Richard J. N.; Woodward, Andrew P.; Mansfield, Caroline (Frontiers in Veterinary Science, 2021)
The aim of this longitudinal microbiome study was to investigate the effects of a commercially available veterinary synbiotic product (Blackmore’s® Paw DigestiCare 60™) on the fecal microbiome of healthy dogs using 16S rRNA gene microbial profiling. Fifteen healthy, privately-owned dogs participated in a two-week trial administration of the product. Fecal samples were collected at different time points, including baseline (prior to treatment), during administration and three weeks after cessation of product use. Large intra- and inter-individual variation was observed throughout the study, but microbiome composition at higher phylogenetic levels, alpha and beta diversity were minimally altered after 2 weeks of probiotic administration. However, the multi-species synbiotic preparation did induce transient changes in the abundance of specific family groups, with the fecal microbiome partially reverting to its baseline state three-weeks after cessation of probiotic administration.